PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI TITIK RINDU COFFEE & VENUE - Mia Agustina; Verry Cyasmoro (Human Capital Development, 2022)
The purpose of this study was to determine whether there is an influence of price perception, product quality and brand image on purchasing decisions at Titik Rindu Coffee & venue. The author uses the Accidental Sampling technique with a sample of 100 respondents with the analysis method using the Structural Equation Modeling (SEM) method with the use of the SmartPLS3 application. This study uses quantitative methods. The population in this study is the consumers of Titik Rindu Coffee & Venue who visited in May-July 2022. The results showed that the perception of price (X1) and product quality (X2) influenced purchasing decisions (Y) positively and significantly. While Brand Image (X3) affects purchasing decisions (Y) positively but not significantly. Keywords : Price Preception, Product Quality, Brand Image, Purchasing Decisions